Bocio endémico - Degrossi, Osvaldo Jorge; Pecorini, Victorio; Altschuler, Noé (Comisión Nacional de Energía Atómica; Argentina, 1970)
Fil: Degrossi, Osvaldo Jorge Comisión Nacional de Energía Atómica; Argentina